Water for Energy and Fuel Production - Shah, Yatish T. (Taylor & Francis, 2014)
Water, in all its forms, may be the key to an environmentally friendly energy economy. Water is free, there is plenty of it, plus it carries what is generally believed to be the best long-term source of green energy-hydrogen. Water for Energy and Fuel Production explores the many roles of water in the energy and fuel industry. The text not only discusses water's use as a direct source of energy and fuel-such as hydrogen from water dissociation, methane from water-based clathrate molecules, hydroelectric dams, and hydrokinetic energy from tidal waves, off-shore undercurrents, and inland waterways-but also: Describes water's benign application in the production of oil, gas, coal, uranium, biomass, and other raw fuels, and as an energy carrier in the form of hot water and steam Examines water's role as a reactant, reaction medium, and catalyst-as well as steam's role as a reactant-for the conversion of raw fuels to synthetic fuels Explains how supercritical water can be used to convert fossil- and bio-based feedstock to synthetic fuels in the presence and absence of a catalyst Employing illustrative case studies and commercial examples, Water for Energy and Fuel Production demonstrates the versatility of water as a provider of energy and fuel, conveying the message that as energy demand and environmental concerns grow, so should our vigilance in pursuing the role of water in the energy landscape.